The Effectiveness of Pertamina's BBM One Price Program in Equalizing Energy Access in 3T Regions: Underdeveloped, Frontier, and Outermost Areas - Alfian Hadi Saputra; Sapto Pramono; Zainal Fatah; Sri Roekminiati (International Journal of Social Science and Humanity, 2025)
Disparities in energy access across Indonesia's underdeveloped, frontier, and outermost (3T) regions have long hindered equitable national development. In response, Pertamina launched the BBM Satu Harga program, aiming to equalize fuel prices and availability throughout these regions. This study explores the effectiveness of the program in achieving its intended goals. Employing a qualitative descriptive approach, the research utilizes in-depth interviews, field observations, and document analysis as primary data collection methods. Informants include Pertamina officials, BBM Satu Harga gas station operators, and community members residing in 3T areas. Data were analyzed using an interactive model, encompassing data condensation, data display, and conclusion drawing. The findings indicate that the BBM Satu Harga program significantly improved energy accessibility, reduced travel distances for fuel acquisition, and received generally positive evaluations from stakeholders. Operational challenges remain, particularly concerning logistical distribution and infrastructure maintenance in remote locations. Nonetheless, the program’s annual implementation targets were largely achieved, affirming its critical role in reducing energy disparities. It is concluded that the BBM Satu Harga program has been effective in fostering more equitable energy access within Indonesia’s most isolated regions. Future research should focus on long-term socioeconomic impacts of energy accessibility and explore strategies to optimize logistical support and infrastructure resilience in 3T regions.